2013
DOI: 10.1371/journal.pone.0084559
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Complexity and Biodiversity: The Multi-Layered Evolutionary History of a Log-Dwelling Velvet Worm in Montane Temperate Australia

Abstract: Phylogeographic studies provide a framework for understanding the importance of intrinsic versus extrinsic factors in shaping patterns of biodiversity through identifying past and present microevolutionary processes that contributed to lineage divergence. Here we investigate population structure and diversity of the Onychophoran (velvet worm) Euperipatoides rowelli in southeastern Australian montane forests that were not subject to Pleistocene glaciations, and thus likely retained more forest cover than system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
0
19
1
Order By: Relevance
“…Such regions are known to promote lineage differentiation, particularly in low-mobility taxa (e.g. Garrick et al, 2008;Thomas & Hedin, 2008;Walker et al, 2009;Bull et al, 2013). If population fragmentation is a recurrent process, then some lineage splitting events will be relatively young and are therefore unlikely to be faithfully tracked by gene trees of both species (Maddison, 1997;Templeton, 2002;Garrick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such regions are known to promote lineage differentiation, particularly in low-mobility taxa (e.g. Garrick et al, 2008;Thomas & Hedin, 2008;Walker et al, 2009;Bull et al, 2013). If population fragmentation is a recurrent process, then some lineage splitting events will be relatively young and are therefore unlikely to be faithfully tracked by gene trees of both species (Maddison, 1997;Templeton, 2002;Garrick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Specimens of both sexes can be maintained in the laboratory for several years at 17-18 °C in plastic jars fi lled with a 2-3 cm layer of peat covered with damp paper towels to retain moisture (Baer and Mayer 2012 ). The species covers a wide geographic range and can be collected easily from decaying logs within and around national parks throughout Tallaganda (New South Wales, Australia), where it is highly abundant (Reid 1996 ;Curach and Sunnucks 1999 ;Barclay et al 2000a , b ;Sunnucks et al 2000 ;Bull et al 2013 ). In the last two decades, E. rowelli has become the most studied onychophoran species (Blaxter and Sunnucks 2011 ), Anterior is left.…”
Section: Euperipatoides Rowelli : An Emerging Model For Developmentalmentioning
confidence: 99%
“…A pitfall trapping study by Nalepa & Grayson (2011) confirmed that large nymphs, sub-adults, and adults do occasionally move between logs. Population genetic studies have repeatedly shown that dispersal distances of wingless saproxylic invertebrates are often very short (e.g., Sunnucks et al, 2006; Garrick et al, 2007; Garrick et al, 2008; Leschen et al, 2008; Marske et al, 2009; Walker et al, 2009; Bull et al, 2013), and this is also likely to be true of C. punctulatus  (Nalepa et al, 2002). Accordingly, following colonization of an uninhabited log by a male or female woodroach, potential mates probably arrive only from logs within close proximity.…”
Section: Introductionmentioning
confidence: 99%